Structural and relational factors for successful cross-sector collaboration in home visiting: a multiple case study - Venice Ng Williams; Carol Yvette Franco-Rowe; Connie Cignetti Lopez; Mandy A. Allison; Gregory J. Tung (BMC, 2024)
Abstract Background Aligning delivery and financing systems across sectors to create broader systems of care can improve the health and well-being of families experiencing adversities. We aimed to identify structural and relational factors for best practices to achieve successful cross-sector collaboration among home visiting programs in the United States. Materials and methods We used a multiple case study approach to identify best practices for successful cross-sector collaboration between home visitors and other community service providers. We selected five diverse exemplary cases with cross-sector collaboration with variation in implementing agency type and geographic location. Cases were selected using a positive deviance approach based on strong coordination and integration with different community service provider types identified from previous survey data. We conducted in-depth qualitative interviews with home visiting staff, community providers, and clients with a total of 76 interviews conducted from 2021 to 2022. We wrote memos to synthesize themes within each case through data triangulation using interview data, documents, and site visit observations. We compared themes across the five cases to create a cross-case synthesis of best practices for successful cross-sector collaboration. Results Across the five cases, relational factors including leadership from all levels, champions across sectors, and shared goals between community providers were key factors for successful collaboration. Interpersonal relationships, coupled with the desire and capacity to engage, facilitated effective coordination to address families' needs. At the structural level, shared data systems, written agreements, and co-location enabled care coordination activities. Community Advisory Boards provided a venue for developing partnerships, relationship-building, resource-sharing, and increasing awareness of home visiting. Conclusions We identified key elements of successful cross-sector collaboration across five case studies where home visitors coordinate care frequently and/or are structurally integrated with a range of providers. These learnings will inform future interventions to improve home visiting collaboration with other community providers to create a system of care to enhance family well-being.